GAMBARAN PENINGKATAN KEPATUHAN PENDERITA TUBERKULOSIS (TB) SETELAH MENGIKUTI FAMILY SUPPORT GROUP THERAPY DI RUMAH SAKIT KHUSUS PARU RESPIRA UPKPM YOGYAKARTA - , MEGA NUR AMALIA, Akhmadi, S.Kp., M.Kes., M.Kep., Sp. Kom ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Background: Tuberculosis (TB) is still a serious health problem throughout the world, including Indonesia. Still the case ( multi-drug resistent ) MDR TB or drug resistance and success rate below standart in Yogyakarta , indicating that there are TB patients who do not adhere to treatment. Therefore strategies to improve adherence of TB patients need to continue to be developed . Family support affects the compliance of TB patients . One effort to improve family support is through a family support group therapy Objective: To determine the effect of the Family Support Group Therapy treatment adherence in patients with TB Methods : This study is a quasi experiment with pretest and post-test one group design with no control group with a qualitative approach . Data collection was conducted from June 2013 to September 2013 through compliance questionnaires and indeepth interview . Samples were taken by purposive sampling as many as 8 TB patients . Results : Analysis of compliance per sub variables showed that there is an adherence improvement to taking tuberculosis medication, diet, prevent transmission, keeping the environment and smoking cessation after Family Support Group Therapy. Whereas the adherence to controls there is no improvement after family Support Group Therapy . Conclusion : The results showed that there was an improvement in compliance after Family Support Group Therapy because a.